Música caipira e seus espaços de sociabilidade : histórias e causos de quem a pratica na cidade de Uberlândia - MG - Rodrigues, Mylena Moreira (2015)
This master thesis aims to investigate from oral sources (interviews), where and by whom the country music social areas have been frequented as well as the experiences and way of life of these people who now live in the cities. So, it has the intention to survey the current songwritings taken as "hillbillies", especially those written people who lived in the countryside and now live in Uberlândia. We intend to investigate, how the practitioners of country music in the city see music nowadays, taking into account songs commercialization and what they have been "imposing" regarding the modernization of it. The investigation understand country music as a social practice. So, it is of great importance these hillbillies experiences of life to understand the continuities and / or breakages that country music has undergone over the past few years. The research starts from the idea of how "social practices," which carry meanings, feelings and values for people who practice it in the city, give shape and meaning to country music today.